2015
DOI: 10.1146/annurev-physchem-040214-121235
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer–Mediated Singlet Fission

Abstract: Singlet fission, the splitting of a singlet exciton into two triplet excitons in molecular materials, is interesting not only as a model many-electron problem, but also as a process with potential applications in solar energy conversion. Here we discuss limitations of the conventional four-electron and molecular dimer model in describing singlet fission in crystalline organic semiconductors, such as pentacene and tetracene. We emphasize the need to consider electronic delocalization, which is responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
411
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(425 citation statements)
references
References 80 publications
9
411
1
4
Order By: Relevance
“…7 In such systems, photoexcitation to S 1 typically results in rapid decay of the singlet state, via an intermediate state with multiexciton character, resulting in the formation of two T 1 states on adjacent chromophores. [8][9][10][11] In solar energy converters, SF can recoup some of the energy normally lost to thermalisation, as long as the triplet excitons can be efficiently converted to charge carriers. SF is a particularly attractive means of multiple exciton generation for high-efficiency concepts, because unlike nanocrystalline downconverters, the optical gap of SF materials is equal to the onset energy of efficient carrier multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…7 In such systems, photoexcitation to S 1 typically results in rapid decay of the singlet state, via an intermediate state with multiexciton character, resulting in the formation of two T 1 states on adjacent chromophores. [8][9][10][11] In solar energy converters, SF can recoup some of the energy normally lost to thermalisation, as long as the triplet excitons can be efficiently converted to charge carriers. SF is a particularly attractive means of multiple exciton generation for high-efficiency concepts, because unlike nanocrystalline downconverters, the optical gap of SF materials is equal to the onset energy of efficient carrier multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Numerous investigations have revealed that the interaction between the initial singlet exciton (SE) state and TT state, which plays an important role in SF dynamics, may include a direct statestate interaction and an indirect superexchange interaction mediated by a charge-transfer (CT) state. 3,4,[22][23][24][25][26][27][28][29][30][31][32] This interaction in organic crystals can be strong enough to induce the quantum coherence between SE and TT states, 5,7,33,34 resulting in an ultrafast timescale of SF.…”
Section: Introductionmentioning
confidence: 99%
“…In tetracene crystals, where SF is endoergic but still highly efficient, the reverse processtriplet−triplet upconversionreadily follows, resulting in delayed fluorescence. 11,12 While most studies to date have addressed SF processes in small-molecular crystals of films, a few reports have been dedicated to intermolecular and even intramolecular SF in solution. Walker et al, 13 for example, report the occurrence of singlet exciton fission in a 6,13-bis (triisopropylsilylethinyl)-pentacene (TIPS-pentacene) excimer in solution.…”
Section: Introductionmentioning
confidence: 99%